Therapeutic effects of traditional Chinese medicine Hua-Feng-Dan in a rat model of ischemic stroke involve renormalization of gut microbiota - He, Xiaoxia; Yuan, Xiaofeng; Shu, Qilin; Gao, Yayang; Chen, Youli; Liu, Yao; Xu, Jian; Zhang, Yongping; Cao, Guoqiong (Frontiers in Pharmacology, 2025)
Hua-Feng-Dan is a traditional Chinese medicine used to treat ischemic stroke, but little is known about its therapeutic mechanism. This study explored whether and how the mechanism involves readjustment of gut microbiota. Rats were subjected to middle cerebral artery occlusion as a model of ischemic stroke or to sham surgery, then treated or not with Hua-Feng-Dan. The different groups of animals were compared in terms of neurological score, cerebral infarct volume, brain edema, brain and gut histopathology to assess stroke severity. They were also compared in terms of indices of intestinal barrier permeability, inflammation and oxidative stress, brain metabolites as well as composition of the gut microbiota and their metabolites. Hua-Feng-Dan significantly reduced cerebral infarct volume and brain water content and improved neurological score, ischemic brain histopathology, and gut histopathology. It partially reversed stroke-induced intestinal barrier disruption and leakage, inflammation, dyslipidemia and oxidative stress, as well as the stroke-induced increase in pathogenic gut microbiota (e.g., Escherichia-Shigella, Enterococcus, Clostridium_innocuum_group) and decrease in beneficial microbiota (e.g., Lachnospiraceae, unclassified__f__Lachnospiracea and Ruminococcus_torques_group). The treatment altered levels of 39 and 38 metabolites produced during gut microbial and brain tissue metabolism respectively, mainly of amino acids, nucleosides, short-chain fatty acids, and essential fatty acids. Levels of factors related to inflammation and intestinal barrier permeability correlated positively with relative abundance of Escherichia-Shigella and Clostridium_innocuum_group, and negatively with 4-(glutamylamino) butanoate, 2-hydroxy-3-methylbutyric acid, dihomo-α-linolenic acid, dihomolinoleic acid, and 10-nitrolinoleic acid. Conversely, levels of 4-(glutamylamino) butanoate, 2-hydroxy-3-methylbutyric acid, and 10-nitrolinoleic acid correlated positively with relative abundance of unclassified__f__Lachnospiracea. Our results suggest that Hua-Feng-Dan may mitigate ischemic stroke injury by renormalizing gut microbiota and restoring gut barrier function, gut metabolism, thereby helping to alleviate inflammatory, neurological damage, and brain metabolic disorders.